Early onset of scleromyxedema Arndt‐Gottron associated with a monoclonal gammapathy: Successful treatment with intravenous immunoglobulins - Asma Kefi; Fatima Jaziri; Khaoula Ben Abdelghani; Sami Turki (Clinical Case Reports, 2022)
Abstract Arndt‐Gottron (S‐AG) syndrome or scleromyxedema is a scarce disease characterized by a generalized papular and sclerodermoid eruption and systemic manifestations that can lead to significant morbid‐mortality. Interesting, S‐AG can be associated with a paraprotein. We report an exceptional scleromyxedema case associated with a benign monoclonal gammapathy in an old woman.